Associations Between Vertebral Marrow Proton Density Fat Fraction and Risk of Prostate Cancer - Li, Shaojun; Wang, Bo; Liang, Wenwen; Chen, Qi; Wang, Wei; Mei, Jiangjun; Zhang, He; Liu, Qianqian; Yuan, Mingyuan (Frontiers in Endocrinology, 2022)
Bone marrow adipocytes may be responsible for cancer progression. Although marrow adipogenesis is suspected to be involved in prostate carcinogenesis, an association between marrow adiposity and prostate cancer risk has not been clearly established in vivo. This work included 115 newly diagnosed cases of histologically confirmed prostate cancer (range, 48–79 years) and 87 age-matched healthy controls. Marrow proton density fat fraction (PDFF) was measured by 3.0T MR spectroscopy at the spine lumbar. Associations between marrow PDFF and risk of prostate cancer by stage of disease and grade sub-types, were performed using multivariable polytomous logistic regression. There were no significant group differences in the vertebral marrow PDFF, despite prostate cancer patients having 6.6% higher marrow PDFF compared to the healthy controls (t = 1.429, P = 0.161). After adjusting for various clinical and demographic characteristics, we found that elevated marrow PDFF was related to an increased risk of high-grade prostate cancer (Odds ratios [OR] = 1.31; 95% confidence interval [CI] 1.08–1.57; P = 0.003). Likewise, increased marrow PDFF had a significantly positive correlation with aggressive prostate cancer risk (OR = 1.54; 95% CI 1.13-1.92; P <0.001). There were no associations between marrow PDFF and low-grade (P = 0.314) or non-aggressive (P = 0.435) prostate cancer risk. The data supports the hypothesis that marrow adiposity was correlated with increased risk of aggressive prostate cancer, supporting a link between adipogenesis and prostate cancer risk.